Students’ Perception of Using Generation Global Application for Speaking Skill in English Club: A Study at Senior High School 2 Padang - Devarizal, Vanni; Sari, Senorica Yulia (Universitas Negeri Padang, 2024)
This article explores generation global application to students speaking skills in English club. The purpose of this research was to know students perception about English skills that construct on GGA and the features of GGA that used in English club activities. This research employed descriptive and quantitative methods. The researcher used a questionnaire to collect data. The participants were 30 students who joined the English club. According to research findings, the students’ perceptions of using GGA for speaking skill in English club is positive considering speaking components in GGA skill and features. GGA skills components include active speaking, active listening, and critical thinking had postive perception by the students in English club. Either, GGA features include teaching resources, video conference, ultimate dialogue adventure and special project had positive perception by the students